Pengukuran Kualitas Performasi Organisasi pada Perusahaan Jasa dengan Menggunakan Total Quality Manajement (TQM) Berbasiskan Mccarthy dan Keefe di PT Prima Jaya Baru Sidoarjo - Susilo, Tri (Jurnal Aplikasi Manajemen, 2009)
PT Prima Jaya Baru Sidoarjo constitutes moving firm at service area, which is construction service that work project kind sort, as enlargement of province road, connecting bridge makings among sylvan. About problem which happens is corporate have never been done measurement aloning to performansi's quality its organization as a whole. To the effect this research is subject to be know performansi's zoom organization in order to increase Human Resource Quality so gets to be known by dimension and dimension sub that needs to get priority for remedial and dimensioning and dimension sub that needs to be kept. This research utilize method full scale quality management where that measurement can thru do six main dimensions which is planning, culture, management of the workforce, performance measurement and feedback, system processes and outcomes. Subs observational result include dimensioning sub enough category and good: tight observation with authority division each of 47.8%, measure and valuate performance measurement & feedback as big as 62.5%, leadership quality step-up as big as 105.6%, dimensioning sub sub that included adverse category and has to be done by support repair for quality to talk shop and person life as big as 10.9%, work load quality training as big as 11.9%, appreciation and promotion as big as 11.7%.